In-depth glycoproteomic characterisation of grape berry vacuolar invertase using a combination of mass spectrometry-based approaches. (1st June 2016) - Hovasse, Agnès; Alayi, Tchilabalo Dilezitoko; Van Dorsselaer, Alain; Marchal, Richard; Jégou, Sandrine; Schaeffer-Reiss, Christine
Highlights: Full characterisation of the N -glycosylated grape vacuolar invertase was performed. MS-based glycoproteomic approach dedicated to highly glycosylated proteins was made. Twelve sites of glycosylation were identified and 12 glycoforms were characterised. Data to a better understanding of invertase glycosylation impact on wine properties. Abstract: Vacuolar invertase is a key enzyme of sugar metabolism in grape berries. A full characterisation of this highly N -glycosylated protein is required to help understand its biological and biochemical significance in grapes. We have developed a mass spectrometry (MS)-based glycoproteomic approach wherein deglycosylated peptides are analysed by LC–MS/MS, while intact glycopeptides are characterised using a dedicated MS method to determine the attachment sites and micro-heterogeneity. For grape invertase, in parallel with deglycosylated peptides analysis, different enzymatic digestions were performed and glycopeptide detection was improved by enrichment method, nanoLC–MS and oxonium glycan ions. This MS-based glycoproteomic approach demonstrates that vacuolar invertase is glycosylated at all twelve potential N -glycosylation sites. Glycosylation is heterogeneous, with twelve glycoforms identified at six of the sites. The identification of several types of N -glycans is a major result to correlate with the surface and foaming properties of wine, the solubility, allergenicity, and protease resistance of wine proteins.